Preparation and characterization of PVC based polymer electrolytes for Proton batteries / Siti Khatijah Deraman - Deraman, Siti Khatijah (Institute of Graduate Studies, UiTM, 2015)
Searching a new material for the development of proton conducting polymer electrolytes that can be used in protonic electrochemical cells is the focus of this research study. In this study, the proton conducting polymer electrolytes were prepared by solution cast technique. Poly (vinyl chloride) PVC is used as the polymer host, ammonium triflate (NH₄CF₃SO₃) as the doping salt and ethylene carbonate (EC) and butyltrimethyl ammonium bis trifluoromethyl sulfonyl imide (Bu₃MeNTf₂N) is used as the plasticizers. Characterization techniques of EIS, XRD, FTIR, FESEM, DSC, TGA, transference number and linear sweep voltammetry measurements were used to study the properties of the PVC based proton conducting polymer electrolytes. Pure PVC exhibits room temperature ionic conductivity of 1.55 × 10⁻¹⁰ S cm⁻¹.Various combinations of PVC and NH₄CF₃SO₃ compositions were attempted and the highest conductivity achieved was 2.50 × 10⁻⁷ S cm⁻¹ when 30 wt. % NH₄CF₃SO₃ (A4) was incorporated into PVC which is an increase of about three orders of magnitude. The increase in conductivity with addition of NH₄CF₃SO₃ is attributed to increase in number of mobile ions and decrease in crystallinity of the films as shown by XRD, FESEM and DSC results. A further increase in ionic conductivity is observed when the polymer-salt electrolyte with the highest conductivity (A4) was added with plasticizers EC and Bu₃MeNTf₂N…